Howey Should be Distributing Cryptocurrencies: Applying the Howey Test to Mining, Airdropping, Forking, and Initial Coin Offerings - Van Adrichem, Benjamin (Science and Technology Law Review, 2019)
The purpose of this Note is to determine which cryptocurrency initial distribution methods involve the offering of securities as regulated by the 1933 Securities Act. The primary legal issue is the Howey test. This test identifies whether an offering is an investment contract, and thus subject to regulation by the 1933 Securities Act, based on whether it involves an investment of money in a common enterprise, in which investors are led to expect profits from the efforts of a promoter or third party. The distribution methods discussed are mining, airdropping, forking, and initial coin offerings (“ICOs”). Mining, airdropping and forking are likely not investment contracts, but initial coin offerings likely are. However, regulators should make it clear that mining, airdropping and forking are acceptable practices. Furthermore, they should proceed with a light touch when regulating initial coin offerings, except in the case of fraud. In particular, the ICO community in partnership with government should instigate a system where ‘crypto-underwriters’ vet ICOs and the crypto-underwriters are regulated by the SEC.